A viral-specific CD4+ T cell response protects female mice from Coxsackievirus B3 infection - Pattnaik, Aryamav; Dhalech, Adeeba H.; Condotta, Stephanie A.; Corn, Caleb; Richer, Martin J.; Snell, Laura M.; Robinson, Christopher M. (Frontiers in Immunology, 2024)
Biological sex plays an integral role in the immune response to various pathogens. The underlying basis for these sex differences is still not well defined. Here, we show that Coxsackievirus B3 (CVB3) induces a viral-specific CD4 + T cell response that can protect female mice from mortality. We found that CVB3 can induce expansion of CD62L lo CD4 + T cells in the mesenteric lymph node and spleen of female but not male mice as early as 5 days postinoculation, indicative of activation. Using a recombinant CVB3 virus expressing a model CD4 + T cell epitope, we found that this response is due to viral antigen and not bystander activation.Finally, the depletion of CD4 + T cells before infection increased mortality in female mice, indicating that CD4 + T cells play a protective role against CVB3 in our model. Overall, these data demonstrated that CVB3 can induce an early CD4 response in female but not male mice and further emphasize how sex differences in immune responses to pathogens affect disease outcomes.